Radiological and Clinical Outcome of Thoracolumbar Burst Fracture Following Short Segment and Long Segment Pedicle Screw Fixation - Ong, Lik Han; Mohamad Amin, Mohamad Zaki; Johan Chin, Mohd Shafiee; Faruk Senan, Nur Aida (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: The indications for operative treatment and type of stabilization procedures for the treatment of thoracolumbar fracture remains controversial. Long-segment pedicle screw fixation permits correction of kyphotic deformity while short-segment pedicle screw fixation preserves motion segments, reduces costs and time of surgery. Our aim is to study the correlation and comparison between clinical and radiological outcome of both fixations and identify factors that might contribute to the outcome. MATERIALS AND METHODS: 60 patients with thoracolumbar spine fracture from 2017 to 2022 were identified. Age, gender, mechanism of injury, classification of fracture, duration of hospital stays and one-year post-operative outcome of Visual Analogue (VAS) pain score, and Oswestry Disability Index (ODI) score were documented. Pre- and post-operative AP/Lateral radiographs measurements of local kyphotic angle, Cobb angle were measured. Signs of fixation failure were examined at follow-up. RESULTS: Subjects mean age is 42.4, male predominance (85%) and work-related. The highest incidence was at level of L1 (56.7 %) in the long-segment and 46.7 % in short-segment. Most common injury was burst fracture (AO classification A3 A4 group) due to fall from height. There is shorter hospital stay documented in the short-segment fixation. Radiological outcome measured in both groups were comparable with no signs of fixation failure. Short-segment fixation group also resulted in better clinical and functional outcome at one-year follow-up. CONCLUSION: There is no significant difference in radiologic outcome of Cobb and kyphotic angle in both fixation groups. Short-segment fixation has significantly better clinical and functional outcome post-operative and at 1-year follow up.